Ma’na al-Hub Fi Kitaab al-Hub fi al-Qur’an al-Karim bi Qalam M. Said Ramadhan al-Buthi Istinadan Ila al-Mandzur al-Siimiiya’iy li Roman Jakobson - Amrulloh, Ahmad Yasir; Arifandi, Fathoni (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2022)
Every human being planted by God since birth has a sense of love in his heart. With this feeling, man will be overwhelmed with peace and tranquility. When he knows love, he will choose who should put love first, the father and the father, the acquaintance, or the opposite sex. Or even he chose himself for him to love her. Even in this field, man may sometimes forget to declare his love for the one who instilled love in his heart. It’s Allah the Almighty who instilled love and the Messenger (peace and blessings of Allaah be upon him) was the first to feel this love and this love for man to love Allah. This paper will describe the meaning of love in the book of love in the Holy Quran by Saeed Ramadan Alp and Fold. This paper is a qualitative and descriptive research. Preliminary data are derived from the book